Atraumatic Acromioclavicular Dislocation: A Case Report and Review of the Literature - Nasrat Sadeghi; Pieter Stijn Haen; Ron Onstenk (Case Reports in Orthopedics)
Acromioclavicular dislocation (AC dislocation) is a common injury of the shoulder. In contrast to a traumatic cause, nontraumatic dislocation is very rare. We report on a 17-year-old female that presented with voluntary recurrent dislocation of the right AC joint followed by recurrent pain without instability of the ipsilateral shoulder. Clinical examination showed crepitation as well as palpitation pain and dislocation of the AC joint. There were no symptoms of Marfan or Ehlers-Danlos syndrome as other joint examinations were also negative for hypermobility. Considering age as well as minor complaints, nonoperative treatment by postural therapy without taping was recommended. After one year, the patient experienced fewer symptoms and she was able to participate in daily activities.